2022
DOI: 10.1093/mnras/stac2023
|View full text |Cite
|
Sign up to set email alerts
|

KMT-2021-BLG-0171Lb and KMT-2021-BLG-1689Lb: two microlensing planets in the KMTNet high-cadence fields with followup observations

Abstract: Follow-up observations of high-magnification gravitational microlensing events can fully exploit their intrinsic sensitivity to detect extrasolar planets, especially those with small mass ratios. To make followup observations more uniform and efficient, we develop a system, HighMagFinder, to automatically alert possible ongoing high-magnification events based on the real-time data from the Korea Microlensing Telescope Network (KMTNet). We started a new phase of follow-up observations with the help of HighMagFi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
12
1
Order By: Relevance
“…Pending the development of a more systematic approach, we would advocate running hot chains on all resonant-and near-resonantcaustic solutions. See Yang et al (2022) for a complementary approach.…”
Section: Discussionmentioning
confidence: 99%
“…Pending the development of a more systematic approach, we would advocate running hot chains on all resonant-and near-resonantcaustic solutions. See Yang et al (2022) for a complementary approach.…”
Section: Discussionmentioning
confidence: 99%
“…For degenerate solutions, Yang et al (2022) suggested that the phase-space factors can be used to weight the probability of each solution. We follow the procedures of Yang et al (2022) and first calculate the covariance matrix, C, of ( a s q log , log , ) from the MCMC chain. Then, the phase-space factor is…”
Section: Preamblementioning
confidence: 99%
“…This paper is the third in our series that aims to publish all by-eye planet detections from the 2021 Korea Microlensing Telescope Network (KMTNet; Kim et al 2016) observing season. Previously, in Ryu et al (2022a) and Ryu et al (2022b), we published eight planet detections; 10 other planets from the 2021 season have been published in other work (Han et al 2022a(Han et al , 2022b(Han et al , 2022c(Han et al , 2022dYang et al 2022).…”
Section: Introductionmentioning
confidence: 86%
“…In addition to the s † (or offset) degeneracy, 2L1S models may be subject to a degeneracy in ρ * , which may affect the value of q (Ryu et al 2022a;Yang et al 2022). Typically, the degeneracy between the two solutions arises because the observed duration of a "bump" anomaly may be controlled either by the width of the caustic (so ρ * is small in comparison) or the size of the source (so ρ * is  the width of the caustic).…”
Section: Degenerate Solutionsmentioning
confidence: 99%